2022
DOI: 10.1080/22221751.2022.2027218
|View full text |Cite
|
Sign up to set email alerts
|

Genomic epidemiology and characterisation of penicillin-sensitive Staphylococcus aureus isolates from invasive bloodstream infections in China: an increasing prevalence and higher diversity in genetic typing be revealed

Abstract: Many countries have reported increasing rates of penicillin-susceptible methicillin-sensitive Staphylococcus aureus (MSSA-PEN S ). To date, there is relatively little known about the current situation and molecular characteristics of MSSA-PEN S in China. In this study, we carried out a laboratory-based multi-region retrospective study to investigate the genomic epidemiology and characterisation of MSSA-PEN S isolated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…The dataset includes 20 different authors from Asia (n = 13), Africa (n = 5), Europe (n = 1) and America (n = 1). A total of 20 studies were included in this synthesis: seven studies employed polymerase chain reaction (PCR) for diagnosing MRSA ( 6 , 9 , 10 , 12 , 13 , 19 , 22 ), one study employed deoxyribonucleic acid (DNA) Microarray ( 7 ), two studies used DNA sequencing ( 2 , 14 ), Xpert MRSA/SA BC assay (n = 2) ( 8 , 17 ), matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF; n = 2) ( 11 , 18 ), multilocus sequence typing (MLST; n = 4) ( 15 , 20 , 23 , 24 ), GENECUBE (n = 1) ( 21 ) and staphylococcal cassette chromosome mec (SCC mec ) typing (n = 1) ( 16 ). Figure 1 is the diagrammatic flow of the study selection and list of techniques appraised in this review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dataset includes 20 different authors from Asia (n = 13), Africa (n = 5), Europe (n = 1) and America (n = 1). A total of 20 studies were included in this synthesis: seven studies employed polymerase chain reaction (PCR) for diagnosing MRSA ( 6 , 9 , 10 , 12 , 13 , 19 , 22 ), one study employed deoxyribonucleic acid (DNA) Microarray ( 7 ), two studies used DNA sequencing ( 2 , 14 ), Xpert MRSA/SA BC assay (n = 2) ( 8 , 17 ), matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF; n = 2) ( 11 , 18 ), multilocus sequence typing (MLST; n = 4) ( 15 , 20 , 23 , 24 ), GENECUBE (n = 1) ( 21 ) and staphylococcal cassette chromosome mec (SCC mec ) typing (n = 1) ( 16 ). Figure 1 is the diagrammatic flow of the study selection and list of techniques appraised in this review.…”
Section: Resultsmentioning
confidence: 99%
“…It allows a bulk number of nucleic acid sequences in a mixture to be tested and analyzed. The study by Jin and colleagues ( 2 , 14 ) used StaphyType DNA microarray (Abbott [Alere Technologies GmbH], Jena, Germany) and the INTER-ARRAY Genotyping Kit S. aureus (Inter-Array GmbH, Bad Langensalza, Germany) for the detection of MRSA. The study by Senok and colleagues (2021) also reported that DNA microarray exhibited 100% specificity and sensitivity ( 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, genomic epidemiology is also applied to understand other types of diseases, mainly those caused by Escherichia coli [ 153 , 154 ], Shigella spp. [ 155 ], Klebsiella pneumoniae [ 156 ], Corynebacterium diphtheriae [ 157 ], Staphylococcus aureus [ 154 , 158 ], Enterococcus faecalis [ 154 ], and Mycobacterium tuberculosis [ 159 ]. Although this discipline is more developed in bacteria and now in viruses, we can find extensive reports on emerging fungal pathogens [ 160 , 161 , 162 , 163 , 164 ] describing antifungal resistance mechanisms or shared synteny among geographically diverse species.…”
Section: Advances In Genomic Epidemiologymentioning
confidence: 99%
“…On the other hand, genomic epidemiology is also applied to understand other types of diseases, mainly those caused by Escherichia coli [146,147] , Shigella spp. [148], Klebsiella pneumoniae [149], Corynebacterium diphtheriae [150], Staphylococcus aureus [147,151], Enterococcus faecalis [147] and Mycobacterium tuberculosis [152]. Although this discipline is more developed in bacteria and now in viruses, we can find extensive reports on emerging fungal pathogens [153][154][155][156][157] describing antifungal resistance mechanisms or shared synteny among geographically diverse species.…”
Section: Advances In Genomic Epidemiologymentioning
confidence: 99%